Laboratory tests, numerical simulations and design of press-braked S690 high strength steel channel sections under major-axis combined loading - Zhang, Lulu (2023)
Testing and numerical modelling have been conducted to investigate the cross-sectional behaviour and resistances of press-braked S690 high strength steel channel sections under combined compression and major-axis bending. The testing programme included initial local geometric imperfection measurements and twenty major-axis eccentric compression (combined loading) tests. The numerical modelling programme included a validation study, where finite element models were developed and validated against test results, and a series of parametric studies, where the developed finite element models were adopted to generate further numerical data over a wide range of cross-section dimensions and loading combinations. The obtained test and numerical data were used to evaluate the existing design interaction curves for press-braked S690 high strength steel channel sections under combined compression and major-axis bending, as specified in the European code, North American specification, and Australian/New Zealand standard. The evaluation results revealed that the codified design interaction curves led to conservative resistance predictions, owing to the linear shapes and inaccurate end points. Improved design interaction curves featuring more efficient shapes and anchored to more accurate end points were then proposed. The proposed design interaction curves were shown to result in more accurate resistance predictions for press-braked S690 high strength steel channel sections under combined compression and major-axis bending than their codified counterparts. The reliability of the proposed design interaction curves was confirmed by means of statistical analyses.